A 1.3-Myr palaeoceanographic record from the continental margin off Dronning Maud Land, Antarctica - Forsberg, Carl Fredrik; Løvlie, Reidar; Jansen, Eystein; Solheim, Anders; Sejrup, Hans Petter; Lie, Hans Erik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
A 12.5 m long core was retrieved from the continental margin off Dronning Maud Land, Antarctica. Magnetostratigraphy, stable isotopes, 14C accelerator mass spectrometer and amino acid analyses indicate a continuous sediment record going back 1.3 Myr. Comparison of CaCO3 results with those from ODP Site 1089 and an index of North Atlantic Deep Water (NADW) influence in surface waters indicate that NADW upwelled along the Antarctic continental margin during the whole of this period. The mid-Pleistocene transition (1.0^0.6 Ma) was accompanied by an apparent decline in the NADW influence, and was followed by extended carbonate dissolution during the interglacials of marine isotope stages (MIS) 13 and 11. Less extensive periods of dissolution occur at the end of the interglacials younger than MIS 11. While interglacial dissolution is characteristic of the Pacific and Indian oceans, the carbon isotopes return to pre-transition values indicative of renewed NADW upwelling. The concentration of ice-rafted debris may reflect changes in the relative rate of interglacial sedimentation. It is speculated that the high ice rafted debris (IRD) concentrations during interglacials younger than 400 kyr may be due to a reduced relative sedimentation rate of other interglacial components whereas the low concentrations during interglacials before the mid-Pleistocene transition may be due to a higher relative sedimentation rate of these. < 2003 Elsevier B.V. All rights reserved.